Teaching behaviors of student teachers under four treatments involving micro-teaching and interaction analysis - Domingo, Juliana (Uro) 1921-
This study determines the effects of conventional training, training through micro-teaching, training in interaction analysis and combined training in interaction analysis and micro-teaching on student teachers' teaching behaviors. It also determines the type of treatment which resulted to high mean scores for student teachers in certain areas.